Assessment of green tea-enabled iron/calcined bentonite nanocomposites for phosphate removal and recovery - ERKEN, ESRA (My University, 2022)
© 2022 Elsevier Ltd.We suggest using green tea enabled iron nanoparticles supported on calcined bentonite (G-nZVI/B) to remove and recover phosphate from synthetic wastewater. The nanocomposites are proposed as an eco-innovative adsorbent material for wastewater treatment plants. Adsorption columns packed with this novel nanocomposite would help overcome the footprint obstacle of wastewater treatment plants in a cost-effective way. We assessed the effect of various iron (Fe) /calcined bentonite (Cal-B) mass ratios (2 g Cal-B/2 g Fe, 2 g Fe, 2 g Cal-B/0.56 g Fe) and Fe/Green tea extract (GT) volumetric ratios (1/1, 1/0.5, 1/0.1) in 9 different nanocomposites (G-nZVI/B). The nanocomposites were characterized using BET, SEM, TEM, FT-IR, XRD, and XPS. The recipe for the optimized nanocomposite composition was found as follows: NC2 (Fe: 2 g, Calcined bentonite: 2 g, Fe/Green tea extract: (1/0.5) (V/V)). TEM analysis demonstrated that size of the iron nanoparticles (INPs) was within the range of 8-30 nm for NC2. Adsorption isotherms and kinetic models were carried out with the optimized nanocomposite under the following conditions: Room temperature; adsorbent dosage = 5 g/L; initial phosphate concentration: 10-900 mg/L, and contact time = 5-1500 min. The results revealed that the maximum adsorption capacity was 58.60 mg/g using Sips model (R2 = 0.959), and the adsorption rate constant was 23.017 mg/(g.min) using Elovich model (R2 = 0.971). Chemisorption was suggested to be the major mechanism of phosphate removal from an aqueous solution. The adsorption and recovery efficiencies were determined to be 98.60% and 53.48% using 1 g of NC2 with 50 mg/L initial phosphate concentration.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, ÇEVRE; MÜHENDİSLİK, KİMYASAL; KİMYA, UYGULAMALI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, ENVIRONMENTAL; ENGINEERING, CHEMICAL; CHEMISTRY, APPLIED; Kimya Mühendisliği (çeşitli); Fizik Bilimleri; Atık Yönetimi ve Bertarafı; Kirlilik; Proses Kimyası ve Teknolojisi; Chemical Engineering (miscellaneous); Physical Sciences; Waste Management and Disposal; Pollution; Process Chemistry and Technology; Abbreviations GT Green tea; BET Brunauer-Emmett-Teller; BJH Barrett, Joyner and Halenda; Cal-B Calcined bentonite; DH Dollimore and Heal; EDS X-ray spectroscopy; FT-IR Fourier transform infrared; G-nZVI/B Green synthesized iron nanoparticles supported on calcined bentonite; H-J Harkins-Jura; INPs Iron nanoparticles; NRMSE Normalized root mean square error; nZVI Nanoscale zero-valent iron; PFO Pseudo-first order; PSO Pseudo-second order; R-D Radushkevich-Dubinin; Raw-B Raw bentonite; SEM Scanning electron microscopy; TEM Transmission electron microscopy; XPS X-ray photoelectron spectroscopy; XRD X-ray diffraction